Urologic Characteristics and Sexual Behaviors Associated with Prostate Cancer in an African-Caribbean Population in Barbados, West Indies - Anselm J. M. Hennis; Suh-Yuh Wu; Barbara Nemesure; M. Cristina Leske (Prostate Cancer)
Prostate cancer (PC) is the principal malignancy affecting African descent men in the Caribbean and the USA. Disparities in incidence, prevalence, and mortality in these populations are poorly understood. We evaluated the urologic characteristics and sexual behaviors of men with histologically confirmed PC (cases) and age-matched controls in the nationwide Prostate Cancer in a Black Population (PCBP) study conducted in Barbados. Cases were around 1.5 to 3 times more likely to report symptoms of prostatic enlargement, hematuria/hematospermia, and previous prostatitis. Sexually transmitted infections (STIs) were similar among cases (24.5%) and controls (26.7%). First sexual intercourse before the age of 16 was associated with an increased likelihood of both low- (Gleason score < 7; OR 1.63; 95% CI: 1.03–1.66) and high-grade PC (Gleason score ≥ 7; OR 1.82; 1.11–2.99). PC risk decreased with later age of sexual debut (P-trend=0.004). More lifetime sexual partners was associated with increased odds of high grade PC (P-trend=0.02). The contribution of sexual behaviors to the development and the outcomes of PC is likely due to multiple mechanisms, and further study will be necessary to elucidate the underlying pathophysiologic mechanisms in this and similar populations.